Frequent translation of small open reading frames in evolutionary conserved lncRNA regions - Ruiz-Orera, Jorge; Mmar Alba (bioRxiv, 2018)
The mammalian transcriptome includes thousands of transcripts that do not correspond to annotated protein-coding genes. Although many of these transcripts show homology between human and mouse, only a small proportion of them have been functionally characterized. Here we use ribosome profiling data to identify translated open reading frames, as well as non-ribosomal protein-RNA interactions, in evolutionary conserved and non-conserved transcripts. We find that conserved regions are subject to significant evolutionary constraints and are enriched in translated open reading frames, as well as non-ribosomal protein-RNA interaction signatures, when compared to non-conserved regions. Translated ORFs can be divided in two classes, those encoding functional micropeptides and those that show no evidence of protein functionality. This study underscores the importance of combining evolutionary and biochemical measurements to advance in a more complete understanding of the transcriptome.